ENFERBRADEN: Experience in building an application for the prevention and treatment of pressure injuries - Júlia Larissa de Souza Silva; Helena Vitória Silva Pinheiro; Júlia Buonafina da Silva; Maurizene Rodrigues Silva; Izabely Vitória Félix de Lima; Laryssa Rodrigues Alves da Silva; Fernando Ramos Gonçalves (Universidade de Pernambuco, 2021)
Objective: To report the experience of building an application for the prevention and treatment of PPL in ICU patients. Method: This is a descriptive study, an experience report, carried out by nursing students at the Nursing School Nossa Senhora das Graças at the University of Pernambuco (FENSG/UPE), Recife-PE, Brazil. Results: Reiterating the proposal to combine technological innovation and health, ENFERBRADEN was developed in a sequential logic, obeying a line of priorities that provides the user with alternatives for patient registration, suggestions for the prevention and treatment of PPL, scoring according to the scale Bradens, alarm that signals the change of decubitus and verification of the existence of lesions in the treatment systematization. Final considerations: The experience lived by the students favored the deepening of the theme, and the construction of a tool that optimizes the use of resources, reduces costs for the service and promotes quality service.